2019
DOI: 10.1016/j.mee.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 3D microdevices from planar electroplating for the isolation of cancer associated cells in blood

Abstract: Malignant cells detaching from a primary tumor to reach the bloodstream are known as circulating tumor cells (CTCs). Enumeration and molecular characterizations of these cells have been used as prognostic cancer biomarkers. Various in vitro techniques are available to extract these biomarkers from blood samples, although their performances are limited by the amount of blood available for analysis, usually 7.5 mL, and the rareness of these cells as a few per mL. To address this sampling bias we propose a three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…More recently, the work by Kim et al has demonstrated the advantage of placing CTC enrichment systems in aphaeretic conditions for longer periods of time (2 h) to substantially increase the number of isolated cells . Alternatively and along the same line, some techniques for in vivo detection/isolation of CTCs and early recruitment of metastatic cells, have also been reported . Despite that sophisticated methods have been proposed in the field of microfluidics to increase sensitivity (efficiency 80–100%) and selectivity (purity <70%), their intrinsic nature as point‐of‐care platforms limits the processing of large blood volumes (throughput ≤10 mL h −1 ).…”
Section: Current Outlook Of Ctcs In Liquid Biopsymentioning
confidence: 99%
“…More recently, the work by Kim et al has demonstrated the advantage of placing CTC enrichment systems in aphaeretic conditions for longer periods of time (2 h) to substantially increase the number of isolated cells . Alternatively and along the same line, some techniques for in vivo detection/isolation of CTCs and early recruitment of metastatic cells, have also been reported . Despite that sophisticated methods have been proposed in the field of microfluidics to increase sensitivity (efficiency 80–100%) and selectivity (purity <70%), their intrinsic nature as point‐of‐care platforms limits the processing of large blood volumes (throughput ≤10 mL h −1 ).…”
Section: Current Outlook Of Ctcs In Liquid Biopsymentioning
confidence: 99%
“…[5][6][7][8][9] Nevertheless, this singlecomponent photoresist is an electrical insulator and additional secondary treatment, such as electroplating, is required to obtain electrical conductivity. 10,11 This increases the process steps and equipment requirements for applications of this photoresist in devices. With the rise of composite materials, researchers have found that the introduction of fillers into the polymer matrix can produce functional materials with both the fundamental properties of the initial material and characteristics of the fillers.…”
Section: Introductionmentioning
confidence: 99%
“…It has unique and superior properties for applications in devices like sensors, photonic devices, and new nano‐electronics 5–9 . Nevertheless, this single‐component photoresist is an electrical insulator and additional secondary treatment, such as electroplating, is required to obtain electrical conductivity 10,11 . This increases the process steps and equipment requirements for applications of this photoresist in devices.…”
Section: Introductionmentioning
confidence: 99%